2016
DOI: 10.1016/j.susc.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Probing the local electronic structure of the cross-linked (1 × 2) reconstruction of rutile TiO2(110)

Abstract: The electronic structure of cross-linked TiO 2 (110)-(1×2) has been investigated using scanning tunneling spectroscopy (STS) and by monitoring changes in ultraviolet photoelectron spectroscopy (UPS) following exposure of the surface to O 2 . STS reveals two states located in the bandgap, at 0.7 and 1.5 eV below the Fermi level. The population of these two states varies over different parts of the (1×2)reconstructed surface. An addition state at 1.1 eV above the Fermi level is observed at the double link part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…It can be clearly seen that the (1 × 2) structure was formed over a wide area (200 × 200 nm 2 ) of the surface. Some local structures such as single links, double links, and line defects, which have been reported in previous studies [22,27,28,32], are evident on the (1 × 2) surface in Figure 2c. These results confirmed that the (1 × 2) surface prepared in this study is the same surface as in the previous studies [22,27,28,32].…”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…It can be clearly seen that the (1 × 2) structure was formed over a wide area (200 × 200 nm 2 ) of the surface. Some local structures such as single links, double links, and line defects, which have been reported in previous studies [22,27,28,32], are evident on the (1 × 2) surface in Figure 2c. These results confirmed that the (1 × 2) surface prepared in this study is the same surface as in the previous studies [22,27,28,32].…”
Section: Methodssupporting
confidence: 75%
“…For each profile, the positional relationship between the periodic lines and the defect is the same. Previous studies have reported STM imaging visualizing Ti 2 O 3 rows with a bright contrast [22,24,26,28]. Based on these earlier results, the periodic lines with bright contrast in the NC-AFM image can be identified as Ti 2 O 3 rows.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…17 Oxygen can be removed through high temperature annealing or ion sputtering, which are commonly used procedures in sample preparation for surface probe experiments. 18,19 Consequently, many different surface structures of varying defect density and reconstructions have been reported. 16,20,21 It is commonly accepted that excess Ti in the form of interstitial atoms results from oxygen removal, which is a surface mediated effect.…”
Section: Introductionmentioning
confidence: 99%
“…32 The exact atomic structure of the cross-linked reconstruction is still contested, [33][34][35][36] yet proposed models all show strands of missing Ti and O atoms along the [001] direction. 18,34 STM studies of lightly reduced rutile TiO 2 (110) surface show isolated oxygen vacancies. 16,21,32,37,38 To form the cross-linked reconstruction vacancies must coalesce, but the exact mechanism of this process is yet unclear.…”
Section: Introductionmentioning
confidence: 99%